2023
DOI: 10.3390/rs15123034
|View full text |Cite
|
Sign up to set email alerts
|

SAR Coherence in Detecting Fluvial Sediment Transport Events in Arid Environments

Abstract: Coherence change detection (CCD) is a remote sensing technique used to map phenomena that, under certain conditions, can be directly related to changes in Interferometric SAR (InSAR) coherence. Mapping the areas affected by sediment transport events in arid environments is one of the most common applications of CCD. However, the reliability of these maps remains an unsolved issue. This paper focuses on verifying that InSAR coherence is indeed able to detect all the fluvial sediment transport events that have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The geometric decorrelation depends on the perpendicular baseline and the local slope of the surface, so it is not correlated with time but its distribution in space is constant. On the other hand, the soil moisture decorrelation, in arid environments, is relevant only during and after rain-and snowfall events (for a few months at most), so it can be located in time [4,19,27]. Regarding the spatial dimension, it has been found that the quantity of precipitation only affects the duration of the soil moisture decorrelation, not its magnitude [16].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The geometric decorrelation depends on the perpendicular baseline and the local slope of the surface, so it is not correlated with time but its distribution in space is constant. On the other hand, the soil moisture decorrelation, in arid environments, is relevant only during and after rain-and snowfall events (for a few months at most), so it can be located in time [4,19,27]. Regarding the spatial dimension, it has been found that the quantity of precipitation only affects the duration of the soil moisture decorrelation, not its magnitude [16].…”
Section: Methodsmentioning
confidence: 99%
“…The mapping of the area affected by a torrential sediment transport event using CCD requires us to first (i) define the study area, (ii) download the SAR images of the study period (Table A1), (iii) calculate the rasters of InSAR coherence (Equation (1)), and (iv) identify the events that occurred during the study period, i.e., the dates when such events happened and the duration of the temporal soil moisture decorrelation. These steps were already carried out in a previous work [27], and the results are used here as a starting point, i.e., input data (Figure 3a). Then, with the rasters of coherence, the dates of the events, and the duration of the temporal effects related to each event, i.e., the soil moisture decorrelation, the procedure is different for each method (Figure 3):…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations